Do Sex Hormones Underlie Sex Differences in Cancer Incidence? Testing the Intuitive in Esophageal Adenocarcinoma. (8th February 2020) - Petrick, Jessica L.; Cook, Michael B.
Abstract: Esophageal adenocarcinoma (EA) incidence is 4–8 times higher in men compared with women, yet this imbalance cannot be explained by known risk factors. This issue of The American Journal of Gastroenterology features results from only the second prospective study to assess whether prediagnostic sex steroid hormones underlie sex differences in EA. Xie et al. report that higher concentrations of testosterone and luteinizing hormone were associated with decreased EA risk. While contrary to the long-standing hypothesis that testosterone increases EA risk, these important results lay a foundation for additional studies to further elucidate this intuitive, intriguing, and evolving hypothesis.